An Optimized Strategy for Self-Assembly of Carbon Nanotubes Arrays: From the Perspective of Molecular Dynamics Simulation and Experiments. Issue 208 (12th June 2020) - Zhang, Jianwei; Wei, Fengqi; Cheng, Yang; Mei, Huanhuan; Wang, Xuewen
Abstract: Hydrophilic/hydrophobic self-assembly has been recognized as one of the effective strategies for assembling carbon nanotubes (CNTs) arrays, but it takes a long time to accomplish this task. So since the emergence of this method, scientists have been exploring how to shorten the assembly process. Meanwhile, up to now, little progress has been made on the mechanism of patterned self-assembly of CNTs. In this paper, in view of the proposal that the assembly of CNTs is able to be accomplished only by hydrophilic functionalization of the substrate, the feasibility of this scheme is verified by molecular dynamics simulation and experiments. Specifically speaking, single-walled carbon nanotubes (SWNTs) with better properties are taken as the research object, and the morphology of surfactant molecule on the surface of SWNTs after non-covalent modification, the optimal model of hydrophilic functionalized substrates (H-substrates) and the morphological changes after the interaction between modified SWNTs (M-SWNTs) and H-substrates are studied by molecular dynamics simulation. At the same time, experiments corresponding to the simulation steps are carried out. The results show that only hydrophilic functionalization of the substrate can also complete the assembly of CNTs, in which the electrostatic attraction between surfactant molecules and H-substrates is the driving force for self-assembly of SWNTs onto hydrophilic surface, and intervention of H2 O molecules between M-SWNTs and bare SiO2 substrates is the main reason why SWNTs cannot be assembled onto bare SiO2 surface. The results provide an optimization strategy for the fabrication of CNTs arrays based on self-assembly method.